PERANCANGAN APLIKASI CUSTOMER SERVICES BERBASIS WEB MENGGUNAKAN METODE MVC (MODEL VIEW CONTROLLER) PADA SONIC KOMPUTER MAKASSAR - Dave Georgie Samuel Sowo; Syafri Arief; Hamdan Arfandy (KHARISMA Tech, 2018)
This research objectives is to application MVC (Model View Controller) concept into Costumer Service system development in Sonic Komputer Makassar. This system developed using MVC (Model View Controller) where using PHP as programing text and MySQL as database. MVC (Model View Controller) concept using to input and display of problems and suggest from employee to costumer whom claimed reparation service. Its evaluation showing value of development system where using MVC (Model View Controller) concept into PHP script, where this system can development to help costumer to send any problems and suggest about their computer.